Henrietta Green: New Country Kitchen - D., J.M. (Petits Propos Culinaires, 1994)
Henrietta Green: New Country Kitchen: Conran Octopus, London, 1994: ISBN 1 85029 366 X: 256 pp, lots of colour photographs by Jess Koppel, index, p’back, £9.99 (also available in hard cover).